Application of machine learning algorithms to evaluate the influence of various parameters on the flexural strength of ultra-high-performance concrete - Qian, Yunfeng; Sufian, Muhammad; Hakamy, Ahmad; Farouk Deifalla, Ahmed; El-said, Amr (Frontiers in Materials, 2023)
The raw ingredients effect on the flexural strength (FS) of cementitious material is an intricate mechanism, particularly in the case of ultra-high-performance concrete (UHPC) due to the involvement of several inter-dependent variables in UHPC for the development of strength. In this digital era, novel artificial intelligence (AI) approaches especially machine learning (ML) techniques are gaining popularity for predicting the properties of concrete composites due to their better precision than typical regression models. In addition, the developed ML models in the literature for FS of UHPC is very limited having limited input parameters. Hence, this research aims to predict the FS of UHPC considering extensive input parameters (21) and evaluate each their effect on its strength by applying advanced ML approaches. Consequently, this paper involves the application of ML approaches, i.e., Support Vector Machine (SVM), Multi-Layer Perceptron (MLP), and Gradient Boosting (GB), to predict the FS of UHPC. The GB approach is more effective in predicting the FS of UHPC precisely than the SVM and MLP algorithms, as evident from outcomes of the current study. The ensembled GB model determination coefficient (R2) is 0.91, which is higher than individual SVM with 0.75 and individual MLP with 0.71. Moreover, the precision of applied models is validated by employing the k-fold cross-validation technique. The validity of algorithms is ensured by statistical means, i.e., mean absolute error and root mean square errors. The exploration of input parameters (raw materials) impact on FS of UHPC is also made with the help of SHAP analysis.